Development of E-Comic Mathematics with Nuance of Religious Values and Critical Thinking of Geometry Material in Junior High School - Cahyono, Budi; Setyawati, Rina Dwi; Rohman, Muhammad Aunur (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2025)
The low interest of Junior High School (SMP/MTs) students in reading textbooks results in many students having difficulty learning geometry material, and impacts students' low critical thinking skills. This study attempts to develop interactive learning media as e-comic media based on religious values, critical thinking, and contextual problems that are valid, practical, and effective. The development method uses the stages of defining, designing, developing, and disseminating (4D Method). The study subjects were material experts, media experts, teachers, and students at MTs Askhabul-Kahfi Semarang. The instruments in this study used expert validation questionnaires, practicality questionnaires, and critical thinking ability test questions. Data processing used the Independent Samples t-test statistical test with SPSS. The study results stated that e-comics are suitable for use because they are stated to be very valid, practical, and effective in increasing the average value of critical thinking skills.